Two-step sequence of acetalization and hydrogenation for synthesis of diesel fuel additives from furfural and diols. - Patil, Anil; Shinde, Suhas; Kamble, Sanjay; Rode, Chandrashekhar, V (Energy & Fuels, 2019)
Acetalization of diols with furfural and subsequent hydrogenation of acetal products provided potential fuel additives that could be blended into commercial diesel. Glycerol could be an interesting polyol for acetalization with furfural due to its low cost, and it is produced as a byproduct in very large amount in the process of biodiesel production. In this work, glycerol acetalization with furfural has been selected as a model reaction. Acetalization reaction was performed under neat conditions (solventless) with 1:1 molar ratio of furfural and glycerol at room temperature over various acid catalysts, including homogeneous and heterogeneous acids. Among several catalysts, Zr-Mont, a heterogeneous solid acid having controlled acidity, gave as high as 78% isolated yield of acetal products. Interestingly, acetal products can be isolated in pure form by performing extraction using cyclohexane that enables selective extraction of product, and unreacted glycerol and furfural were left in aqueous phase, which can be recycled. Further, to make fuel components from isolated acetal product of glycerol and furfural, hydrogenation was performed over a series of supported noble-metal catalysts under low H-2 pressure at room temperature. Among them, 5% Pd/C showed very high activity for ring hydrogenation that resulted in high yield of hydrogenation products. However, hydrogenated product contains free hydroxyl group that needs to be subsequently etherified or acetylated. Interestingly, etherified derivative was obtained in high yield compared to acetylated derivative. In addition, several other diols were treated with furfural and their products were subsequently hydrogenated over 5% Pd/C under very low H-2 pressure. The properties of resulting compounds were investigated so as to find most suitable candidates as additives to commercial diesel.

Tetraalkylammonium-based dicationic ionic liquids (ILs) for CO2 capture - Kulkarni, Prashant S.; Ranjane, Prathamesh; Mishra, Karun; Sundararajan, Swati; Kamble, Sanjay (New Journal of Chemistry, 2023)
This investigation includes the synthesis and characterization of a new series of ionic liquids (ILs) based on the tetraalkylammonium dication for the absorption of CO2, a step towards the development of more efficient and sustainable technologies. It was possible to synthesize amine-substituted PEG diacrylate by modifying poly(ethylene glycol) (PEG), which was then quaternized with 1-bromopentane to produce the IL PDBr. The other IL products, PDNTf2, PDBF4 and PDPF6, were synthesized via the metathesis of PDBr with the appropriate salt. The synthesized products were characterized using various techniques, such as FTIR, H-1 and C-13 NMR, elemental analysis, and density and viscosity meters, and evaluated as potential sorbents for CO2 capture. DSC and TGA were used to examine the thermal properties of the ILs. As observed from their thermal degradation behavior, the ILs exhibited two-stage disintegration with thermal stability up to 150 & DEG;C. The pressure drop method was used to study the sorption capacity of the ILs towards CO2. The sorption investigation showed that when the pressure is increased, the CO2 absorption increases. Equilibrium is reached in 40 minutes, demonstrating a rapid absorption rate. The IL with the [BF4](-) anion (PDBF4) demonstrated a maximum sorption capacity of 0.577 mole fraction of CO2, and can be regenerated and reused efficiently with less than 0.5% variation from its original absorption capacity. The CO2 absorption capacity for the ILs with other anions follows the trend: Br & AP; NTf2 < PF6 < BF4. This work shows that tetraalkylammonium-based dicationic ILs are adaptable, making them a suitable material for many applications, including sustainable CO2 capture technology.